English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

This is how far i got:
ORIGINAL EQUATION: 6x+6(4)=3x-2
6x+24=3x-2

2007-11-20 10:17:37 · 5 answers · asked by Sarah B 1 in Science & Mathematics Mathematics

5 answers

6x + 24 = 3x - 2
6x = 3x - 2 - 24
6x - 3x = - 2 - 24
3x = - 26
x = - 26 / 3

2007-11-24 08:07:04 · answer #1 · answered by Como 7 · 0 0

Hi sarah

Try this:

6x +6(4) = 3x -2 ; ok , first simplify
6x + 24 = 3x -2 ; now get x on one side by taking 3x away from both

3x + 24 = -2 now subtract 24 from both
3x = - 26 ; now divide both sides by 3
x = -26/3

Hope that helps

2007-11-20 18:23:24 · answer #2 · answered by pyz01 7 · 0 0

6x + 6(4) = 3x - 2 Mult. 6X4

6x + 24 = 3x - 2 Add 2 from each side

6x + 26 = 3x Sub. 6x from each side

26 = -3x or -3x = 26 Div. by -3

x = -26/3

2007-11-20 18:24:02 · answer #3 · answered by guitarman 2 · 0 0

6x+24=3x-2
3x=-26
x=-26/3

I did the shortcut for 6x+24=3x-2 by subtracting 3x in both sides and 24 in both sides.

2007-11-20 18:20:41 · answer #4 · answered by Anonymous · 1 0

just simplify
you sub tract s4 from each side
6x=3x-26 (since we subtracted 24 from negative 2)
then subtract the 3x from each side
it becomes
3x=-26
so divide each by three
x=-26/3

see?

2007-11-20 18:23:03 · answer #5 · answered by Anonymous · 0 0

fedest.com, questions and answers